2005
DOI: 10.1038/sj.jhh.1001838
|View full text |Cite
|
Sign up to set email alerts
|

Brachial–ankle pulse wave velocity: an index of central arterial stiffness?

Abstract: Brachial-ankle pulse wave velocity (baPWV) is a promising technique to assess arterial stiffness conveniently. However, it is not known whether baPWV is associated with well-established indices of central arterial stiffness. We determined the relation of baPWV with aortic (carotid-femoral) PWV, leg (femoral-ankle) PWV, and carotid augmentation index (AI) by using both cross-sectional and interventional approaches. First, we studied 409 healthy adults aged 18-76 years. baPWV correlated significantly with aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
337
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(356 citation statements)
references
References 18 publications
17
337
0
2
Order By: Relevance
“…29 Carotid-femoral PWV has been accepted as a standard method to evaluate aortic stiffness, and evidence is accumulating that an increased carotid-femoral PWV measurement is associated with increased cardiovascular morbidity and mortality. 4,5,30 baPWV, a new measure of arterial stiffness, provides qualitatively similar information to that obtained from aortic PWV, an index of central arterial stiffness, 31 although the baPWV value reflects a combination of elastic and muscular arterial stiffness. Sclerotic changes in peripheral muscular arteries may also be a risk factor associated with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 71%
“…29 Carotid-femoral PWV has been accepted as a standard method to evaluate aortic stiffness, and evidence is accumulating that an increased carotid-femoral PWV measurement is associated with increased cardiovascular morbidity and mortality. 4,5,30 baPWV, a new measure of arterial stiffness, provides qualitatively similar information to that obtained from aortic PWV, an index of central arterial stiffness, 31 although the baPWV value reflects a combination of elastic and muscular arterial stiffness. Sclerotic changes in peripheral muscular arteries may also be a risk factor associated with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 71%
“…It has been shown that baPWV correlates closely with directly measured aortic PWV and carotid–femoral PWV used as the criterion standard for noninvasive assessment of central arterial stiffness 33, 34. Compared with the measurement of carotid–femoral PWV requiring a skilled technique and exposure of the inguinal region during measurement, baPWV measurement is a simple method using a separate oscillometric cuff for each of the 4 extremities.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we detected BaPWV, which has been shown to be closely correlated with the aortic PWV. 19 As we known, advancing age and BP are the main factors leading to arterial stiffening. Nevertheless, in the present study, we have identified significant negative correlations between salusin-alpha levels and BaPWV after proper adjustment for age and BP values.…”
Section: Salusin-alpha Is Associated With Preclinical Atheroscleroticmentioning
confidence: 99%
“…Although the BaPWV has been shown to be closely correlated with the aortic PWV, it also includes peripheral muscular arterial stiffness. 19 BaPWV may be a less ideal measure of large artery stiffness than central PWV. In the future study, aortic (or carotidfemoral) PWV should be measured.…”
Section: Salusin-alpha Is Associated With LV Diastolic Dysfunction Inmentioning
confidence: 99%